Caracterizações sociodemográficas dos domicílios poligâmicos e não poligâmicos no Benim, em 2013; Burkina Faso, em 2006; e Togo, em 2010. - Abdoul Razack Mamoudou (2022)
In African countries, like other regions of the world, different demographic regimes and stages of demographic transition coexist, although the responsibility of the region, exclusively subSaharan Africa, is recognized for most of the world's population growth in the coming decades. However, the context of Francophone Africa presents both in rhythm and trajectory, important heterogeneities in demographic variables. In addition, there are cultural aspects that impose on society certain practices and behaviors that can shape demographic dynamism. For example, marriages, which often have the purpose of procreation, can affect the behaviors of fertility and mortality in a society. In most of the demographic literature on this region, many try to discard the weight of the cultural differential complex to discuss trends. Therefore, the objective of this study was to characterize women in polygamous households of border countries (Benin, Togo and Burkina Faso) regarding their sociodemographic and cultural characteristics considering the regions and administrative subdivisions in the last available demographic censuses of each country. Based on this, the following specific objectives were defined: to review the theoretical approaches on polygamy; to analyze the proportions of polygamous women, as well as the distribution in the territory considering sociodemographic variables and administrative subdivisions (Benin, Burkina Faso, and Togo); and to analyze the possible impact of practice on sociodemographic characteristics. The research used Ipums-I data from 2013, 2006 and 2010 respectively from Benin, Burkina Faso and Togo for descriptive and exploratory analysis. The results reveal that there is a predominance of non-polygamous women in relation to polygamous women in all age groups in Benin and Togo, except in old age in Burkina Faso. A disproportionality in the practice of polygamy is emphasized both in countries and at subregional levels. That is, polygamy has different proportions, being higher in Burkina Faso, then in Benin, and finally in Togo. In addition, polygamous women have a lower socioeconomic, home and educational profile compared to the non-polygamous profile. For example, in addition to all countries presenting predominance of polygamous women in rural areas and with incomplete primary education, the proportions of polygamous women were higher for those who did not have electricity, sewers, television and bathroom. Meanwhile, women's behaviors via the curves of the Specific Rates of Marital Fertility in Benin and Burkina Faso are very similar and diverge from Togo women. For the TEFM curve of polygamous in Togo was a level below and cool from that of monogamous. Meanwhile, the curves of Benin and Burkina Faso were very close and glued to almost the same level among these women. Finally, practice is associated with sociodemographic variables. This association was negative for age groups, education levels, Christian religion and for some sub-regions, consequently the odds ratios differ. It can be said that being Christian, having a living child, owning electricity, bathroom, or knowing how to read and write, for example, reduces the reason for the chance of being polygamous. However, the models indicated that so many variables of household, religious, socioeconomic and sub-regional characteristics had positive or negative association on polygamy.